Investigation of RNA‐RNA Interactions Using the RISE Database. Issue 1 (8th November 2018) - Ju, Yanyan; Gong, Jing; Yang, Yucheng T.; Zhang, Qiangfeng Cliff
Abstract: RNA‐RNA interactions (RRIs) are essential to understanding the regulatory mechanisms of RNAs. Mapping RRIs in vivo in a transcriptome‐wide manner remained challenging until the recent development of several sequencing‐based technologies. However, RRIs generated from large‐scale studies had not been systematically collected and analyzed before. This article introduces RISE, a database of the RNA Interactome from Sequencing Experiments. RISE provides a comprehensive collection of RRIs in human, mouse, and yeast, derived from transcriptome‐wide sequencing experiments, as well as targeted sequencing studies and other public databases/datasets. To facilitate better understanding of the biological roles of these RRIs, RISE also offers rich functional annotations involving RNAs, and an interactive interface to explore the analysis results. Here, we provide a brief description of the RISE website and a step‐by‐step protocol for using RISE to study RRIs. © 2018 by John Wiley & Sons, Inc.